Sintering effect on mechanical properties of composites of bovine hydroxyapatite (BHA) and Li2O - Oktar, Faik Nüzhet; Demirer, M. R.; Gündüz, Oğuzhan; Agathopoulos, S.; Peker, I.; Özyeğin, L. S.; Salman, Serdar (Trans Tech Publications Ltd, Brandrain 6, Ch-8707 Zurich-Uetikon, Switzerland, 2006)
In this study, hydroxyapatite (HA) material, obtained from calcinated bovine bone (BHA), was mixed with 0.25, 0.50, 1.00, and 2.00 wt% Li2CO3. The pressed pellets were sintered at various sintering temperatures between 900 degrees C and 1300 degrees C. Measurements of compression strength, microhardness, and density, along with SEM observation and X-ray diffraction analysis were performed. The experimental results showed that the samples with 0.25 and 0.50% Li2CO3 reached a maximum of densification and the highest values of compression strength and microhardness were achieved after sintering at 1300 degrees C. The wetting effect of a Li2O-associated glassy phase was observed even from 900 degrees C.
Keywords: bovine derived hydroxyapatite; lithium oxide; sintering; mechanical properties; Ceramics